The Influence of Depth-Dependent Seasonal Temperature Variability on Growth Signal in Arctica islandica - Caldarescu, Diana E.; Brey, Thomas; Abele, Doris; Beierlein, Lars; Lohmann, Gerrit; Ionita, Monica (Frontiers in Marine Science, 2021)
Bivalve sclerochronological records with annually resolved growth bands are applicable proxies in reconstructing features of the hydro-climate system. Here we evaluate the relationship between growth indices of A. islandica, previously collected at approximately 82 m depth in the North Atlantic, and seasonal subsurface temperature at various depths for the 1900-2005 period. Correlations with sea surface temperature at the collection site are not significant during winter and weak for the remaining seasons. The strongest in-phase correlations persist for summer and autumn below 56 m water depth, whereas weaker correlations are lagged by one or two years. We also observe similarities with distant water bodies in the North Atlantic sector, and a corresponding large-scale oceanographic pattern that increases significantly with water depth along the trajectory of the North Atlantic Current. We suggest that by investigating the relationship with the temperature signal at various depths locally and at large-scale increases the reliability and application of bivalve shells as marine archives.